A circularly polarized low‐profile magnetoelectric dipole antenna. Issue 11 (20th July 2021) - Wu, Siyu; Zhao, Jianping; Xu, Juan
Abstract: In this article, we proposed a novel circularly polarized magnetoelectric (ME) dipole antenna with low profile, which is excited by substrate integrated waveguide aperture‐coupled feeding structure with a butterfly‐shaped slot. The ME dipole antenna is formed of a couple of oblong metallic patches with square corner cutting off and elliptic perturbation acting as electric dipole, and two couples of vertical metalized via holes working as magnetic dipole. The profile of the antenna is 0.122λ0 . The antenna achieves a fractional bandwidth of 32.6% for |S11| smaller than −10 dB from 22.6 to 31.3 GHz and the 3‐dB axial‐ratio bandwidth (BW) of 12.8% from 22.6 to 25.7 GHz. Moreover, the gain is maintained over 6 dB for a large portion of the operational BW. The measured boresight gain is 7.8 dB.